2014
DOI: 10.3390/s140916343
|View full text |Cite
|
Sign up to set email alerts
|

Role of Morphological Structure, Doping, and Coating of Different Materials in the Sensing Characteristics of Humidity Sensors

Abstract: The humidity sensing characteristics of different sensing materials are important properties in order to monitor different products or events in a wide range of industrial sectors, research and development laboratories as well as daily life. The primary aim of this study is to compare the sensing characteristics, including impedance or resistance, capacitance, hysteresis, recovery and response times, and stability with respect to relative humidity, frequency, and temperature, of different materials. Various ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 198 publications
(319 reference statements)
2
57
0
Order By: Relevance
“…[ 33,47,51 ] These designs have response times ranging from 10 ms [ 48 ] to 0.5 min [ 49 ] and have resolutions up to 0.01%RH across a broad range. [ 33,47 ] In recent years, there has been a concerted drive to produce sensing elements that can be integrated with nano-and microscale optical circuitry, to comply with lab-on-a-chip devices and other emerging technologies. Gas sensors have been constructed based upon whispering gallery resonators, [ 52 ] gas sensitive photonic crystals, [ 53 ] nanowires above sensitive polymer fi lms, [ 54,55 ] specially fabricated nanoparticles, [ 7,38 ] and nanoparticles embedded in polymer optical nanofi bers.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 99%
See 2 more Smart Citations
“…[ 33,47,51 ] These designs have response times ranging from 10 ms [ 48 ] to 0.5 min [ 49 ] and have resolutions up to 0.01%RH across a broad range. [ 33,47 ] In recent years, there has been a concerted drive to produce sensing elements that can be integrated with nano-and microscale optical circuitry, to comply with lab-on-a-chip devices and other emerging technologies. Gas sensors have been constructed based upon whispering gallery resonators, [ 52 ] gas sensitive photonic crystals, [ 53 ] nanowires above sensitive polymer fi lms, [ 54,55 ] specially fabricated nanoparticles, [ 7,38 ] and nanoparticles embedded in polymer optical nanofi bers.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 99%
“…The most common type of humidity sensor is an electrochemical design with a water-reactive fi lm placed between two electrodes, have shown high sensitivities, with impedance changes of several orders of magnitude with RH [41][42][43][44][45] and response times usually around several seconds. [ 46,47 ] The most common optical sensors take the form of optical fi bers coated with a reactive material, which changes the confi nement of the mode in response to RH. [ 33,47,51 ] These designs have response times ranging from 10 ms [ 48 ] to 0.5 min [ 49 ] and have resolutions up to 0.01%RH across a broad range.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Humidity sensor is a kind of device that is sensitive to ambient humidity, because some of the measurable physical properties change due to the water absorption [1]. They have gained increasing attention in applications for industrial processing and daily lives such as food quality and storage, meteorological studies, environmental humidity for air conditioning systems, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Harizanov et al reported that BaTiO 3 thin films are stuck well on silicon and fused silica substrates and provide evenly and smoothly coating [3]. In humidity sensing, silicon-based materials contribute good response towards humidity measurement [4]. Chien-Tsung et al found that porous silica substrate gives better humidity sensing properties as better trapping of polar type water molecules is achievable with large number of pores on surface [5].…”
Section: Introductionmentioning
confidence: 99%